Development Of Berapak Composite As A Core Material For High Resilient Sports Equipment - Soovirehn, a/l Epeng; Mastika, Lamat; Muhammad Firdaus, Abong Abdullah (UNIMAS Publisher, 2018)
The berapak (bamboo internal skin) is a material produced from bamboo that has the potential to be made as the alternative materials to replace timber and polymers. Studies by researchers have shown that berapak material is suitable for manufactured products with high endurance like bicycle frameworks and automotive components. Research identifying the potential of this material is still at its early stages. Experiments with different types of adhesives have shown variations in terms of strengths and compression levels. There are three samples produced to test the berapak material resistance level. The first sample consists of 100% berapak material, the second sample is of a carbon fibre composite and the third sample is of a glass fibre composite. Results from the tests carried out indicate there are differences in the resistance level, sample weight and test graphs.